1993
DOI: 10.1063/1.109421
|View full text |Cite
|
Sign up to set email alerts
|

X-ray characterization of Si δ-doping in GaAs

Abstract: High-resolution triple-axis x-ray diffractometry has been used to examine the structural properties of a δ-doped superlattice of sixty periods, each consisting of half a monolayer of Si and 500 Å of GaAs, grown by molecular beam epitaxy (MBE) at 400 °C under an arsenic flux. The measurements indicated that the superlattice was of high structural quality. Using dynamical simulation, it was demonstrated that the period variation was equal to 3%, while the silicon spreading was no greater than 2 monolayers. It wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
12
0

Year Published

1995
1995
2001
2001

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 31 publications
(13 citation statements)
references
References 10 publications
1
12
0
Order By: Relevance
“…The deviations observed in higher-order features were expected and are due to a combination of interface broadening, associated primarily with multilayer 2D growth as shown by RHEED, and small variations in layer thicknesses. 17 From further simulations, it appears that the latter effect, which can be minimized by a better growth-rate control, dominates. Similar HR-XRD rocking curves, with satellite peaks up to nϭϪ5, were obtained for all samples.…”
mentioning
confidence: 95%
“…The deviations observed in higher-order features were expected and are due to a combination of interface broadening, associated primarily with multilayer 2D growth as shown by RHEED, and small variations in layer thicknesses. 17 From further simulations, it appears that the latter effect, which can be minimized by a better growth-rate control, dominates. Similar HR-XRD rocking curves, with satellite peaks up to nϭϪ5, were obtained for all samples.…”
mentioning
confidence: 95%
“…At first the wafer was cleaned with H 2 at a temperature of 1100°C, and then a 5.0 nm Si buffer layer was grown at 625°C. Subsequently, a 2.2-nm-thick Si 1Ϫx Ge x film was grown by deposition of GeH 4 and SiCl 2 at 625°C. Finally, a 280 nm Si capping layer was deposited at 700°C.…”
Section: Methodsmentioning
confidence: 99%
“…[1][2][3] With high-resolution XRD it is possible to characterize depositions of less than 1 ML, when they are grown in a superlattice structure; i.e., to analyze a sub-ML-thickness film, 60 periods are needed. 4 However, the semiconductor devices mentioned above contain only one nanofilm.…”
Section: Introductionmentioning
confidence: 99%
“…For Si 8-doping of GaAs (00 1) at 400°C, it is well known that Si atoms preferentially occupy Ga sites, and it has been suggested that they form two-dimensional (2D) islands [1][2][3][4][5][6][7][8]9]. Recent reflectance anisotropy spectroscopic (RAS) measurements for the deposition of Si at 400 °C onto the more As-rich c(4 x 4) surface also support this picture [14].…”
Section: Discussionmentioning
confidence: 65%
“…The experiments were carried out at low deposition temperatures (400 °C) in order to minimize the effects of bulk diffusion and segregation of Si which can occur during any subsequent GaAs overgrowth. In effect, this simulates the ideal situation for the formation of 8-doped structures for which the confinement of Si atoms in the 8-layers has been shown to be better than 2 ML from the plane [9].…”
Section: Introductionmentioning
confidence: 99%